2019
DOI: 10.1177/0954411919888321
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and precision of cardiac output estimation by an automated, brachial cuff-based oscillometric device in patients with shock

Abstract: Non-invasive monitoring of cardiac output is a technological and clinical challenge, especially for critically ill, surgically operated, or intensive care unit patients. A brachial cuff-based, automated, oscillometric device used for blood pressure and arterial stiffness ambulatory monitoring (Mobil-O-Graph) provides a non-invasive estimation of cardiac output values simultaneously with regular blood pressure measurement. The aim of the study was to evaluate the feasibility of this apparatus to estimate cardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 34 publications
1
14
0
1
Order By: Relevance
“…Though, the use of SphygmoCor, Mobil-o-Graph PWA and other non-invasive devices in ICU patients has been investigated in previous studies; our study is the first one having as primary endpoint checking the feasibility of these methods in respect to central and peripheral blood pressure estimation and using as comparison the invasive blood pressure values. [11][12][13][14][15] Moreover, unlike previous studies, our study population consisted entirely of patients with septic or cardiogenic shock with the vast majority of them receiving catecholamines and no mechanical assistances such as intra-aortic balloon pump. Non-invasive assessment failure was more pronounced with the SphygmoCor XCEL.…”
Section: Discussionmentioning
confidence: 99%
“…Though, the use of SphygmoCor, Mobil-o-Graph PWA and other non-invasive devices in ICU patients has been investigated in previous studies; our study is the first one having as primary endpoint checking the feasibility of these methods in respect to central and peripheral blood pressure estimation and using as comparison the invasive blood pressure values. [11][12][13][14][15] Moreover, unlike previous studies, our study population consisted entirely of patients with septic or cardiogenic shock with the vast majority of them receiving catecholamines and no mechanical assistances such as intra-aortic balloon pump. Non-invasive assessment failure was more pronounced with the SphygmoCor XCEL.…”
Section: Discussionmentioning
confidence: 99%
“…In a recently published study from Athens [16], CO was measured in 24 patients in shock at the intensive care unit invasively (thermodilution) and non-invasively with the method we describe, i.e. brachial-cuff derived pressure waveforms and dedicated ARCSolver algorithms.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding accuracy, many studies have sought to determine the accuracy of the Mobil‐O‐Graph 24h PWA device for measuring brachial BP, 9,10 central BP, 4,11 wave reflections, 12,13 estimated aortic pulse wave velocity, 14,15 and stroke volume 16,17 in adults. Taken together, all studies showed at least a reasonable agreement with the reference standard.…”
Section: Hemodynamic Variable Change From Daytime To Nighttime (“Dippmentioning
confidence: 99%